Lower Supply and Higher Demand: Why Aren’t Processed Oranges Prices Higher? - Ariel Singerman (EDIS, 2022)
Production of processed oranges in Florida has been decreasing almost every year since HLB was found. Driven by the outbreak of COVID-19, demand for orange juice has increased in recent months. Even though prices have increased as a consequence of such market dynamics, they are not at break even level for the average grower. The culprit for prices not being at a higher level is that the quality of fruit in Florida has been declining significantly as a consequence of HLB. Thus, processors have been increasingly blending higher quality imported juice with Florida juice to meet the USDA standard.